Developing A Valued Attitude Towards the Family in Students as A Topical Pedagogical Problem - Sherzodbek Ismoilov (Zien Journals, 2021)
This article provides recommendations for educating young people in the spirit of love for the family, high respect and reverence for our traditions and traditions
Keywords: family; homeland; tradition; nationality